Our Experience in Using a Low Dose CT as a Screening of Lung Cancer - Dineva, Stoyanka; Pavlova, Adelina; Getsov, Plamen (International Journal For Research In Health Sciences And Nursing, 2017)
Lung cancer is one of the leading cause of death among all cancer types, killing approximately 34 000 people per year. By the time symptoms develop, the tumour is often at an advanced stage and the prognosis is bleak. Treatment at a less advanced stage of disease by surgical resection has been shown to substantially reduce mortality. Screening would be attractive if it could detect presymptomatic lung cancer at a stage when surgical intervention is feasible but has been the subject of scientific debate for the past three decades. Low-dose CT scan screening greatly improves the likelihood of detecting small nodules and, thus, of detecting lung cancer at a potentially more curable stage.